God’s Blessing for His People: An Exegetical Study of Numbers 6:22–27 - Susanto Dwiraharjo (Scriptura Indonesia, 2026)
Religious communities have their own ways of ending worship, often through blessings. One of the most common in Christian tradition is the benediction found in Numbers 6:22–27, known as the “Aaronic Blessing.” This passage has become central in many churches, repeated so often that its wording is rarely changed. While this shows its importance, it can also cause people to hear it only as a routine ending rather than a meaningful proclamation. This study aims to help believers rediscover the depth of the blessing by using the method of exegesis. This involves reviewing literature, analyzing the text, and organizing insights into themes. By paying attention to both the meaning of the words and their historical context, the blessing can be understood in a way that speaks to life today. The results show that the Aaronic Blessing is more than a ritual conclusion. It is a powerful declaration of God’s favor, protection, and peace. When understood fully, it becomes a source of spiritual growth, guiding believers to apply its message in daily life and deepening their relationship with God.